2013
DOI: 10.1177/0146167213497592
|View full text |Cite
|
Sign up to set email alerts
|

Touch as an Interpersonal Emotion Regulation Process in Couples’ Daily Lives

Abstract: Interpersonal touch seems to promote physical health through its effects on stress-sensitive parameters. However, less is known about the psychological effects of touch. The present study investigates associations between touch and romantic partners' affective state in daily life. We hypothesized that this association is established by promoting the recipient's experience of intimacy. Both partners of 102 dating couples completed an electronic diary 4 times a day during 1 week. Multilevel analyses revealed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
183
1
10

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 209 publications
(229 citation statements)
references
References 52 publications
14
183
1
10
Order By: Relevance
“…Jones and Yarbrough (1985) stated that a handshake, an encouraging pat on the back, a sensual caress, a nudge for attention, a tender kiss, or a gentle brush of the shoulder can all convey a vitality and immediacy that is at times far more powerful than language. According to App et al (2011), touch is the preferred non-verbal communication channel for conveying intimate emotions like love and sympathy, confirmed by, for instance, Debrot et al (2013) who showed that responsive touch between romantic partners enhances their affective state.…”
Section: Touch Physiological Functioning and Wellbeingmentioning
confidence: 94%
“…Jones and Yarbrough (1985) stated that a handshake, an encouraging pat on the back, a sensual caress, a nudge for attention, a tender kiss, or a gentle brush of the shoulder can all convey a vitality and immediacy that is at times far more powerful than language. According to App et al (2011), touch is the preferred non-verbal communication channel for conveying intimate emotions like love and sympathy, confirmed by, for instance, Debrot et al (2013) who showed that responsive touch between romantic partners enhances their affective state.…”
Section: Touch Physiological Functioning and Wellbeingmentioning
confidence: 94%
“…This is one of many reasons why the socio-interpersonal context plays an important role in the adaptation to a stressful life event [23]. The romantic partner, as commonly the closest significant other in adulthood, can be seen as a resource when coping with the disease, a phenomenon referred to as dyadic coping [24] in general, and when it comes to the emotional processing of the event in the dyad as interpersonal emotion regulation [25]. A key strategy of interpersonal emotion regulation is disclosure - the verbal sharing of thoughts and feelings [26].…”
Section: Adjustment Disorder As Stress-response Syndromesmentioning
confidence: 99%
“…Furthermore, if disclosure is followed by a responsive reaction of the listening partner it triggers the establishment of psychological closeness or intimacy, and improves relationship quality. Relationship quality in turn has raised more and more attention in the scientific community as an important predictor of a more adaptive adjustment to stressful situations: studies have shown that psychological intimacy and social embedment are associated with positive effect [25], well-being and health [28]. Discussed pathways of this effect are known associations between the social context and neuroendocrine parameters (e.g.…”
Section: Adjustment Disorder As Stress-response Syndromesmentioning
confidence: 99%
“…Frequent partner contact over longer periods of time is also related to general positive affect and psychological well-being [121], and is related to a lower risk of infection with the common cold virus [105].…”
Section: A Touch Of Romance To Calm the Nervesmentioning
confidence: 99%
“…The sad story of the Romanian orphans who received almost no social touch and were much worse off for it, illustrates this need poignantly [77,98,332,374]. Such a craving for touch endures in later life, and most profoundly affects people in a romantic relationship for whom a touch may benefit their overall well-being [121] and immediate responses to stressful events [102,127,345].…”
Section: Mediated Social Touch In Affectionate Interactionsmentioning
confidence: 99%